PENERAPAN ETIKA ADMNISTRASI PUBLIK DALAM PELAKSANAAN TUGAS APARATUR BIROKRASI DI SEKRETARIAT DAERAH KABUPATEN KEPULAUAN TALAUD - HALEAN, SISILYA (Sam Ratulangi University, 2013)
ABSTRACT Civil Service Discipline stipulated in Government Regulation No. 30 of 1980 that was later revised in Government Regulation No. 53 of 2010. The purpose of this study is to investigate the application of public administration ethics / duties of the State in the implementation of the bureaucratic apparatus in the district secretariat Talaud Islands.The method used is descriptive. The focus of this study: Responsibility, Service,; Faithfulness,; Sensitivity, Similarities,; Deserving. Data sources / informants drawn from the number of employees by 10 informants structural officials, and 10 staff employees, the number of informants as many as 20 people. Collecting data using interview techniques.Analysis of the data used is descriptive analysis techniques interaaktif models. Based on the analysis of data drawn the conclusion that the application of ethics in the discharge of public administration that appears on the attitudes and behavior of personnel in performing their duties and responsibilities of office as, devotion, loyalty, sensitivity, equality, and decency in the bureaucratic apparatus regional secretariat Talaud Islands in general carried out effectively.Based on the results of the study generally recommended advice to the government secretariat Talaud Islands region through the implementation of public administration ethics are viewed from the aspect of responsibility, devotion, loyalty, sensitivity, equality and kepantasanya now rightly claim to do the moral or ethical considerations in conducting action intensified to more streamlined.Keywords: Application of the Public Administration Ethics